Fatal attraction of Caenorhabditis elegans to predatory fungi through 6-methyl-salicylic acid - Xi Yu (Nature Portfolio, 2021)
Methyl salicylate ester is a plant metabolite involved in plant-insect and plant-plant interactions. Here, Yu et al. show that a nematode-trapping fungus has potential to produce a related compound, 6-methyl salicylate, which attracts its prey (nematodes) and modulates spore germination and trap formation in the fungus.